ANALYSIS OF INFLUENCING FACTORS THE WILLINGNESS OF MICRO, SMALL AND MEDIUM ENTERPRISESPAY INCOME TAX IN MEDAN CITY - Br Ginting, Silvana Pratiwi (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine the influence of awareness of paying taxes, knowledge of tax regulations and level of education on the willingness to pay taxes at KPP Pratama Medan Petisah. The type of research used in this study is associative research. The population in this study is all individual taxpayers registered with KPP Pratama Medan Petisah as of 2021 as many as 94232 business entities and a sample of 100 business entities. The sampling technique is carried out using purposive sampling techniques. The data analysis techniques used in this study are by using Data Quality Test, Classical Assumption Test, Multiple Liner Regression Analysis and Hypetesis Test (T-test) with SPSS 16 software tools. The results of this study show that awareness of paying taxes and knowledge of taxation have a positive and partial significant influence on the willingness to pay taxes. Medium for education level does not have the effect of dah is not significant on the cost of paying taxes. Together the awareness of paying taxes and knowledge of tax regulations show a significant influence against the will to pay taxes.